OPTIMALISASI KUALITAS PELAYANAN PADA ONLINE STORE (TOKO ONLINE) MELALUI KOMUNIKASI PEMASARAN INTERAKTIF UNTUK MENINGKATKAN LOYALITAS PELANGGAN (Studi Kasus Pada Kualitas Pelayanan www.gramedia.com) - Ferrari Lancia (Jurnal Akrab Juara, 2019)
This study seeks to determine and assess the optimization of service quality that is seen in the improvement and improvement of service quality www.gramedia.com as an online store in maintaining and increasing customer loyalty. The approach in this research is qualitative with the case study method and uses interview techniques, field observations, and documentation. The object of this research is the management of service quality at the Gramedia.com online store as an interactive marketing communication medium to increase customer loyalty. Meanwhile, the subject of this research is the online shop www.gramedia.com which is located in the Matraman area, East Jakarta. Key informants and informants consist of the Marketing Section and the Fulfillment Section contained in the Operations Division, as well as several customers from www.gramedia.com. The results of this study indicate that Gramedia.com uses seven integrated marketing communication tools, including advertising, sales promotion, direct marketing, word of mouth marketing, viral marketing, events, and interactive marketing. This creates interest from potential customers and regular customers, is also able to maintain and even increase customer loyalty through increasing the number of website visitors, followers on social media, and increasing sales figures.